Simulated Hydrological Dynamics and Coupled Iron Redox Cycling Impact Methane Production in an Arctic Soil. Issue 10 (11th October 2022) - Sulman, Benjamin N.; Yuan, Fengming; O'Meara, Teri; Gu, Baohua; Herndon, Elizabeth M.; Zheng, Jianqiu; Thornton, Peter E.; Graham, David E.
Abstract: The fate of organic carbon (C) in permafrost soils is important to the climate system due to the large global stocks of permafrost C. Thawing permafrost can be subject to dynamic hydrology, making redox processes an important factor controlling soil organic matter (SOM) decomposition rates and greenhouse gas production. In iron (Fe)‐rich permafrost soils, Fe(III) can serve as a terminal electron acceptor, promoting anaerobic respiration of SOM and increasing pH. Current large‐scale models of Arctic C cycling do not include Fe cycling or pH interactions. Here, a geochemical reaction model was developed by coupling Fe redox reactions and C cycling to simulate SOM decomposition, Fe(III) reduction, pH dynamics, and greenhouse gas production in permafrost soils subject to dynamic hydrology. We parameterized the model using measured CO2 and CH4 fluxes as well as changes in pH, Fe(II), and dissolved organic C concentrations from oxic and anoxic incubations of permafrost soils from polygonal permafrost sites in northern Alaska, United States. In simulations of repeated oxic‐anoxic cycles, Fe(III) reduction during anoxic periods enhanced CO2 production, while the net effect of Fe(III) reduction on cumulative CH4 fluxes depended on substrate C availability. With lower substrate availability, Fe(III) reduction decreased total CH4 production by further limiting available substrate. With higher substrate availability, Fe(III) reduction enhanced CH4 production by increasing pH. Our results suggest that interactions among Fe‐redox reactions, pH and methanogenesis are important factors in predicting CH4 and CO2 production as well as SOM decomposition rates in Fe‐rich, frequently waterlogged Arctic soils. Plain Language Summary: Methane, a powerful greenhouse gas, is produced in flooded soils that lack oxygen, and its production is sensitive to soil acidity. Methane production could increase as frozen soils in cold regions thaw. Many Arctic soils are also rich in iron, which some soil microorganisms can use instead of oxygen for respiration through iron reduction, which produces carbon dioxide while decreasing soil acidity. Computer models that are currently used to predict greenhouse gas emissions from thawing Arctic soils do not include iron or acidity changes. We built a new model to simulate how iron, oxygen, and carbon interact in soils that are repeatedly flooded. Our model simulations showed that iron reducers can fuel carbon dioxide production when soils are repeatedly flooded. However, the effect of iron cycling on methane production depended on the availability of easily‐decomposable carbon. When iron reducers competed with methane producers for a small amount of available carbon, methane production declined. When easily‐decomposed carbon was abundant, iron reduction enhanced methane production by decreasing soil acidity. Our results suggest that including iron cycling and changes in soil acidity in soil carbon models could improve predictions of the climate warming potential of greenhouse gas emissions from thawing Arctic soils. Key Points: Ferric iron reduction can fuel organic matter decomposition and modulate pH in iron‐rich Arctic soils We coupled iron and carbon cycling and related pH changes in a geochemical reaction model under simulated cycles of oxic‐anoxic conditions Methanogenesis was increased (via rising pH) or decreased (via substrate limitation) by iron reduction depending on substrate availability